Running pronghorn - Kaplan, Nicole, photographer (Colorado State University. Libraries, 2009)
Side view of running pronghorn, not obscured by any vegetation, with white flowers across the SGS.
Keywords: white flowers; SGS; pronghorn; landscapes; plants; animals